The Effect of Locus of Control on Academic Grit in Final Year Students - Ayyistiqamah Saleh; Asniar Khumas; Novita Maulidya Djalal (Lectura : Jurnal Pendidikan, 2023)
Academic grit is a characteristic needed by final year students in order to be able to face all the demands in their lectures. However, preliminary studies and several previous studies show that the academic grit level of students in Indonesia tends to be moderate to low. The purpose of this research is to determine the effect of locus of control on academic grit in final year students. Respondents of this study namely 201 final year students of the faculty of psychology, Universitas Negeri Makassar (UNM) who were in 9, 11, and 13 semesters. Measuring instrument used is the locus of control scale and the academic grit scale. This study used a quantitative methods. Sampling technique used was simple random sampling technique. The data collection technique used was a scale type questionnaire. The data analysis technique used was multiple linear regression analysis. The results showed that there was a positive influence of internal locus of control on academic grit (β =1,568, p = 0,000 ; p < 0,05). There is a negative influence of external locus of control on academic grit (β = -0,476, p = 0,018 ; p < 0,05). Internal locus of control and external locus of control contributed 54.3% to academic grit. This research can be a source of information in designing interventions to improve academic grit by considering the locus of control possessed by students.